Extended-spectrum beta-lactamases among Enterobacteriaceae isolated in a public hospital in Brazil - Dropa, Milena; Balsalobre, Livia C.; Lincopan, Nilton; Mamizuka, Elsa M.; Murakami, Thays; Cassettari, Valéria C.; Franco, Fábio; Guida, Stella M.; Balabakis, Angelica J.; Passadore, Lilian F.; Santos, Silvia R.; Matté, Glavur R.; et al. (Revista do Instituto de Medicina Tropical de São Paulo, 2009)
Extended-spectrum β-lactamases (ESBL) in enterobacteria are recognized worldwide as a great hospital problem. In this study, 127 ESBL-producing Enterobacteriaceae isolated in one year from inpatients and outpatients at a public teaching hospital at São Paulo, Brazil, were submitted to analysis by PCR with specific primers for blaSHV, blaTEM and blaCTX-M genes. From the 127 isolates, 96 (75.6%) Klebsiella pneumoniae, 12 (9.3%) Escherichia coli, 8 (6.2%) Morganella morganii, 3 (2.3%) Proteus mirabilis, 2 (1.6%) Klebsiella oxytoca, 2 (1.6%) Providencia rettgeri, 2 (1.6%) Providencia stuartti, 1 (0.8%) Enterobacter aerogenes and 1 (0.8%) Enterobacter cloacae were identified as ESBL producers. BlaSHV, blaTEM and blaCTX-M were detected in 63%, 17.3% and 33.9% strains, respectively. Pulsed field gel eletrophoresis genotyping of K. pneumoniae revealed four main molecular patterns and 29 unrelated profiles. PCR results showed a high variety of ESBL groups among strains, in nine different species. The results suggest the spread of resistance genes among genetically different strains of ESBL-producing K. pneumoniae in some hospital wards, and also that some strongly related strains were identified in different hospital wards, suggesting clonal spread in the institutional environment.